A MODEL FOR CONSUMER TRUST IN E-COMMERCE - Mohammad Falahat; Yan-Yin Lee; Yi-Cheng Foo; Chee-En Chia (Asian Academy of Management Journal, 2019)
E-commerce has grown rapidly over the past decade and has become a significant trend. One of the major concerns for the successful proliferation of e-commerce is the issue of consumers’ trust in Internet vendors. This study examines the antecedents of trust in e-commerce among Malaysian online consumers. Data was collected from 300 respondents who had recently made online purchases. Structural equation modelling-partial least squares (SEM-PLS) was used to analyse the data, and our findings reveal that brand recognition, service quality, security, and word-of-mouth (WOM) lead to higher levels of consumer trust, whereas customer satisfaction has an insignificant relation to consumer trust. This study enables online vendors or e-commerce business owners to understand consumer demand and satisfy their needs. Strategies need to be set right too to attract more consumers in purchasing online.